Health perceptions, self and body image, physical activity and nutrition among undergraduate students in Israel. - Liat Korn; Ester Gonen; Yael Shaked; Moria Golan (PLoS ONE, 2013)
Purpose This study examines health perceptions, self and body image, physical exercise and nutrition among undergraduate students. Methods A structured, self-reported questionnaire was administered to more than 1500 students at a large academic institute in Israel. The study population was heterogenic in both gender and fields of academic study. Results High correlations between health perceptions, appropriate nutrition, and positive self and body image were found. The relationships between these variables differed between the subpopulation in the sample and the different genders. Engagement in physical exercise contributed to positive body image and positive health perceptions more than engagement in healthy nutrition. Nutrition students reported higher frequencies of positive health perceptions, positive self and body image and higher engagement in physical exercise in comparison to all other students in the sample. Conclusions This study suggests, as have many before, that successful health promotion policy should reflect a collectivist rather than an individualist ethos by providing health prerequisites through a public policy of health-promotion, where the academic settings support a healthy lifestyle policy, by increasing availability of a healthy, nutritious and varied menu in the cafeterias, and offering students various activities that enhance healthy eating and exercise. IMPLICATIONS AND CONTRIBUTION: This study examined health perceptions, self-image, physical exercise and nutrition among undergraduate students and found high correlations between these topics. Nutrition students reported higher frequencies of positive health perceptions, and positive self and body image and engaged more in physical exercise when compared with all other students in the sample.